QUELLING THE RAGING FIRE: RESTORATIVE JUSTICE AS A RESPONSE TO VIGILANTISM IN SOUTH AFRICA - Mokomane, Reliance Bongani (Obiter, 2023)
Vigilantism is a persistent problem in South Africa. The problem largely emanates from people’s dissatisfaction with how the police, or the criminal justice system, deals with crime. There are high levels of crime in communities and the general feeling is that little has been done to curb it. Thus, the acts of vigilantism fill the vacuum left by unsatisfactory law enforcement or the criminal justice system. Although vigilantism constitutes criminal behaviour that warrants punishment, vigilantes are often viewed as proactive citizens fighting crime. Put differently, vigilantism is seen as an attempt by community members to deal with crime. One crime-intervention strategy that involves the community legally in finding appropriate solutions is restorative justice. Accordingly, research indicates that restorative justice has the potential to reduce crime. Given that crime is what triggers vigilantism, there is a reason to believe that restorative justice might eliminate the chances of people resorting to vigilantism. The purpose of this article is to examine restorative justice as a method of dealing with vigilantism in South Africa.